2021
DOI: 10.1002/slct.202103577
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Doped Titanium Dioxide for Environmental Remediation, Hydrogen Evolution and Sensing: A Review

Abstract: Titanium dioxide is an essential photocatalyst for the purification of water and air and energy generation. Titanium dioxide shows relatively high chemical stability and reactivity under ultraviolet light (λ< 387 nm), the energy of which exceeds the 3.3 eV bandgap in the crystalline anatase phase. TiO2 is active under UV light, and its practical applicability is limited under visible light. Modification techniques like metal doping can enhance its activity under visible light. Metal doping is employed for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…[20] Therefore, doping with transition metals such as Cu, Ni, Zn, Co, Fe, and Cd caused the properties of TiO 2 to change for certain and desired applications. [21,22] TiO 2 /Cd structures produced by the electrospinning technique were used as a photocatalyst in the removal of methylene orange dye after the calcination process. As a result of the experiments, it was reported that Cd-doped TiO 2 nanoparticles showed faster photocatalytic efficiency than pure TiO 2 nanoparticles.…”
Section: Doi: 101002/gch2202300271mentioning
confidence: 99%
“…[20] Therefore, doping with transition metals such as Cu, Ni, Zn, Co, Fe, and Cd caused the properties of TiO 2 to change for certain and desired applications. [21,22] TiO 2 /Cd structures produced by the electrospinning technique were used as a photocatalyst in the removal of methylene orange dye after the calcination process. As a result of the experiments, it was reported that Cd-doped TiO 2 nanoparticles showed faster photocatalytic efficiency than pure TiO 2 nanoparticles.…”
Section: Doi: 101002/gch2202300271mentioning
confidence: 99%
“…In particular, TiO 2 can be doped with metal (such as Co, Nb, Mn, Cu, and Ni) or non-metal dopants (such as C, F, and N) [155]. Studies have shown that metal doping can enhance the gas response and selectivity of TiO 2 by altering phase transformation, surface potentials, chemical activity, amount of adsorbed oxygen ions, and regulating charge carrier concentration [156,157].…”
Section: Dopingmentioning
confidence: 99%
“…For many years, TiO 2 has been widely used in solar cells, in photocatalysis, and in lithiumion batteries. [22][23][24][25][26] There are many different crystalline forms of TiO 2 (such as anatase, rutile, and bronze), but anatase and rutile TiO 2 are considered to be the most promising materials for solar cells and photocatalysts. More and more studies have found that when TiO 2 is used as rechargeable battery electrode material, it has better electrochemical cycle stability because of its small volume expansion and stable structure.…”
Section: Introductionmentioning
confidence: 99%